(3GdLeY Hjf GdUdGJjfs - (3ESeGYjd Hf eMeO Hf ESMGb GdMSjfj,J (B1164 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CeQ ai GdOjf HGdELJeGY , hfgi Yf GdJaQb hGdEHJOGY CeG HYO aEf HYV MedI GdYde GdTQja SCdfi Yf COdI ChbGJ GdUdGI s
(3BNQgG (B:s
(3heG PcQfG gPG Yf UGMH GdYhGUe hGdbhGUe EdG Cf GdeNGdajf LejYkG dGjNGdahf Cf UGMH GdbhGUe MLI , hCfg Ydi hGVM GdeMLI CjfeG JhLg hef GdLdSg fSJeO GdCeGfI hgh MSHi hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdCShO GdSejcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B288s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs